PENGARUH KOMITE AUDIT TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN & MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mirnayanti Mirnayanti; Iroh Rahmawati (Jurnal Bina Bangsa Ekonomika, 2022)
The purpose of this study is to determine the role of the audit committee in running the food & beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2019 and to determine the effect of the audit committee on the value of the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014 -2019. The research method used is descriptive quantitative technique and the sampling technique used is purposive sampling method with certain criteria. The population in this study were all manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange, namely 26 companies. Data processing and data analysis techniques include classical assumption test, simple regression analysis, coefficient of determination and statistical hypotheses. Based on the t test, it states that the audit committee has no effect on firm value